Description of the full-grown larva and barcode of Athripsodes taounate taounate Dakki & Malicky 1980 (Trichoptera: Leptoceridae), an Iberic-Maghrebian endemic - Ruiz-García, Antonio; Lara-Rodríguez, Andrés; Garzón, Andrés (Zootaxa, 2024)
In this paper we describe the main morphological characteristics that distinguish the full-grown larva of Athripsodes taounate taounate, an Iberic-Maghrebian endemic. The conspecificity of the larva and adult was confirmed by DNA analysis. Morphological features that discriminate it from the described Iberian-Maghrebian species of Athripsodes are given.